2019
DOI: 10.31571/bahasa.v8i2.1451
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers’ Self-Regulated Learning Strategy, Motivation, and Revision Behaviors in Efl Academic Writing

Abstract: <p>The present study explored pre-service teachers’ self-regulated learning strategy<br />and motivation in EFL academic writing. A further aim of the study is to<br />investigate the relationship between their self-regulated learning strategy and<br />motivation as well as to explore the revision behaviors in English academic<br />writing. A questionnaire was administered to 56 pre-service teachers (PST)<br />majoring English language education. The questionnaire covered 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…As for the utilization of SRW strategies, the overall average score of the section displayed that students' reported use of these strategies was in the slightly-high frequency range. This finding partly supports the previous research that documents moderate to slightly-high use of writing strategies (Abadikhah, Aliyan, & Talebi, 2018;Nabhan, 2019), but it is not much agreement with the earlier studies which reported the medium-level use of writing strategies (Bai & Guo, 2018;Teng, 2016) in different EFL contexts. The possible explanation for participants' not reporting "very high" use of SRW methods might be that many university students are not much exposed to the explicit strategy-based instruction in writing (Teng, 2016;Woodrow, 2011;Zhang, Aryadoust, & Zhang, 2016) and therefore, they may not have enough experience regarding how to benefit from the related strategies or in what contexts those strategies should be implemented, even if they may have an idea of what these strategies refer to (Zhang, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…As for the utilization of SRW strategies, the overall average score of the section displayed that students' reported use of these strategies was in the slightly-high frequency range. This finding partly supports the previous research that documents moderate to slightly-high use of writing strategies (Abadikhah, Aliyan, & Talebi, 2018;Nabhan, 2019), but it is not much agreement with the earlier studies which reported the medium-level use of writing strategies (Bai & Guo, 2018;Teng, 2016) in different EFL contexts. The possible explanation for participants' not reporting "very high" use of SRW methods might be that many university students are not much exposed to the explicit strategy-based instruction in writing (Teng, 2016;Woodrow, 2011;Zhang, Aryadoust, & Zhang, 2016) and therefore, they may not have enough experience regarding how to benefit from the related strategies or in what contexts those strategies should be implemented, even if they may have an idea of what these strategies refer to (Zhang, 2008).…”
Section: Discussionsupporting
confidence: 82%